Implementasi Ta’widh dan Ta’zir dalam Perbankan Syariah: Perspektif Fatwa Majelis Ulama Indonesia - Rahmawati; Juhriaty; Jufrin (Maqasid: Jurnal Studi Hukum Islam, 2025)
Abstract The DSN-MUI fatwa regulates the implementation of ta'widh and ta'zir by taking into account sharia principles, ensuring that the compensation and sanction mechanisms do not contain elements of usury or injustice. From the perspective of maqashid sharia, the implementation of ta'widh and ta'zir aims to safeguard property (hifzh al-mal) and uphold justice in transactions, thereby supporting the achievement of the main objectives of sharia. This study shows that the DSN-MUI fatwa provides a clear legal basis for the implementation of both concepts, maintaining a balance between protecting the rights of transacting parties and the continuity of fair and sustainable sharia banking practices. Using a descriptive qualitative approach and normative analysis, this study explores how the MUI fatwa regulates the implementation of ta'widh and ta'zir and how its implementation is relevant to the main objectives of maqashid sharia, namely safeguarding property, justice, and social balance in Islamic economics.